2008
DOI: 10.1111/j.1525-142x.2008.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐trait evolution in a cave fish,Astyanax mexicanus

Abstract: When surface species colonize caves, a characteristic suite of traits eventually evolves over time, regardless of species. The genetic basis of the inevitable appearance of these very similar phenotypes was investigated through quantitative trait loci (QTL) mapping of 12 traits that differ significantly between the recently evolved (<1 Myr). Mexican cave tetra and its surface conspecific. The traits were a representative set, including eye size, pigment cell numbers, chemical sensitivity, body and skull morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
241
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 176 publications
(260 citation statements)
references
References 48 publications
16
241
3
Order By: Relevance
“…In this regard, multiple causes of eye degeneration are consistent with the recent discovery of as many as 12 quantitative trait loci, and thus genes, governing eye loss in cavefish (Protas et al, 2008). This opens the possibility that several different evolutionary forces could synergistically drive eye regression.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…In this regard, multiple causes of eye degeneration are consistent with the recent discovery of as many as 12 quantitative trait loci, and thus genes, governing eye loss in cavefish (Protas et al, 2008). This opens the possibility that several different evolutionary forces could synergistically drive eye regression.…”
supporting
confidence: 52%
“…In the past, three theories have been proposed to explain the loss of eyes in cave organisms: (1) neutral mutation and genetic drift, (2) positive selection against eyes due to energy conservation or their possible liability and (3) indirect selection against eyes based on increase in beneficial traits that are negatively linked to optic development by pleiotropy. The first idea was favored until about the turn of this century (Culver and Wilkens, 2000), but since then new genetic and developmental evidence has tipped the scale toward the third idea-pleiotropy (Jeffery, 2005;Protas et al, 2008). In this review, Wilkens (2010) re-evaluates the genetic and developmental data and concludes that there is no validity for the second or third (selectionist) theories, reverting to neutral mutation as the most plausible explanation for eye degeneration.…”
mentioning
confidence: 99%
“…This would be expected given the extensive genomic rearrangements that have occurred among even closely related species over the course of genomic evolution. Nonetheless, for several linkage groups (Astyanax LGI 8,11,14,18,21,23,24), we found that every syntenic hit resides on a single Danio chromosome (Danio chromosomes 1, 18, 2, 10, 1, 17, 7, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…1, LGI 10). Many of these genomic markers span the critical region(s) of QTL identified in our phenotypic analyses (14). Thus, the addition of genes to the linkage map can be used directly to seek associations between a gene of interest and a particular trait.…”
Section: Gene Position In Astyanax Is Reliably Predicted By Homologoumentioning
confidence: 99%
See 1 more Smart Citation